KEPATUHAN PENGGUNAAN SIMBOL DAN SINGKATAN MEDIS DALAM BERKAS REKAM MEDIS TERKAIT PERSIAPAN AKREDITASI KARS DI RUMAH SAKIT PANTI RAPIH YOGYAKARTA - , RORO AYU SEKAR M; , Sugeng, SKM ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Unification of medical symbols and abbreviations are as one element in the assessment of accreditation standards KARS chapter of Manajemen Komunikasi dan Informasi (MKI) in Hospital Management group, the goal is that the uniformity of terms that can be understood and written as a means of communication between health professionals. Based on preliminary studies in Panti Rapih Hospital Yogyakarta researchers learned that the Panti Rapih Hospital Yogyakarta in preparation KARS accreditation and already there are guidebooks symbols and abbreviations have been approved by the hospital director. Objective: knowing the staff understanding regarding the use of medical symbol and abbreviations, knowing staff loyalty in the use of medical symbol and abbreviations list standard, knowing the factors inhibiting the implementation of the use of medical symbols and abbreviation, and knowing the attempt to overcome the limiting factor in the implementation of the use of symbols and medical.abbreviations. Methods: The study used type is a descriptive study with a qualitative approach to data collection using observation, interviews, and documentation studies. The study design was cross-sectional. For the validation data using triangulation and triangulation techniques. Sampling the subject and the object of study using purposive sampling. This research was performed at the medical record installation of Panti Rapih Hospital Yogyakarta. Results: Based on the interview, staff understanding regarding the use of medical symbols and abbreviations are still lacking. But the medical record installation of officers already know about the use of symbols and abbreviations. Based on the study of the documentation of compliance staff in the use of symbols and a list of standard abbreviations have good views of the appropriateness of medical symbols and abbreviations in the medical record file with guidebooks symbols and abbreviations apply in Panti RapihHospital Yogyakarta, suitability stands 75.11% was obtained for a number of specialist surgery, 79.42% for specialist obstetric and gynecology, 84.63% for pediatricians, 84.98% for internist. Corresponding symbol is a 100% for each specialist. While a number of abbreviations that are not appropriate for surgeons 24.89%, 19.82% for specialist obstetric and gynecology, 15.37% for pediatricians, and 15.02% for the internist. Inhibiting factors of the elements Man (Human) is less concerned for the medical and nursing staff on the use of medical symbols and abbreviations, the difficulty encountered medical and nursing personnel to clarify, the existence of symbols and abbreviations used without authorized by the director of the hospital, from element method (method ) is the lack of socialization related to the use of medical symbols and abbreviations. Efforts to overcome the limiting factor is the increasing awareness of medical personnel to understand guidebook medical symbols and abbreviations applicable, socialization and hold regular meetings.